Color scheme for decorating a residence - Harris, Maud (My University, 1908)
Introduction: The small word “home” has perhaps a different meaning for each individual, yet to even the most indifferent person it at least signifies a place of rest where one may, to some degree shut out the outside world. But a home in its true sense has come to mean more than a mere house of shelter for it is in the home that we express our true natures…
Citation: Harris, Maud. Color scheme for decorating a residence. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Design; Graduating theses; Senior theses; Theses